2016
DOI: 10.1182/bloodadvances.2016000711
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of the platelet glycoprotein Ib antagonist anfibatide in murine models of thrombotic thrombocytopenic purpura

Abstract: Thrombotic thrombocytopenic purpura (TTP), a potentially fatal blood clot disorder, is primarily caused by severe deficiency of plasma ADAMTS13 activity resulting from acquired autoantibodies. Plasma exchange is the only effective initial therapy. However, the high mortality rate and the complications associated with plasma exchange therapy remain a major concern. To address unmet clinical needs, therapeutic efficacies of anfibatide, a snake venom-derived platelet glycoprotein Ib antagonist, in murine models o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 41 publications
(50 reference statements)
0
15
0
Order By: Relevance
“…Within 20 min (King et al, 2016) Within 20 min (King et al, 2016) Within 20 min (King et al, 2016) 2 h (Ungerer et al, 2011) .4 h (De Luca, 2012) .4 h (De Luca, 2012) 4-8 h (Topol, 1999;Vorchheimer et al, 1999) Half-life 10 h (Gregov et al, 1987) 10-11 h (Eikelboom et al, 2012) 24-36 h (Eikelboom et al, 2012) 20 min (Umemura and Iwaki, 2016) 30 min to 7.5 h (Umemura et al, 2016) 7-9 h (Teng and Butler, 2013) 3-5 min (Sible and Nawarskas, 2017) 5-7 h (murine) (Zheng et al, 2016) Prodrug No Yes (CYP3A5 and CYP2C19) (Yoo et al, 2009(Yoo et al, , 2010 Yes Yes…”
Section: B Adp Receptor Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within 20 min (King et al, 2016) Within 20 min (King et al, 2016) Within 20 min (King et al, 2016) 2 h (Ungerer et al, 2011) .4 h (De Luca, 2012) .4 h (De Luca, 2012) 4-8 h (Topol, 1999;Vorchheimer et al, 1999) Half-life 10 h (Gregov et al, 1987) 10-11 h (Eikelboom et al, 2012) 24-36 h (Eikelboom et al, 2012) 20 min (Umemura and Iwaki, 2016) 30 min to 7.5 h (Umemura et al, 2016) 7-9 h (Teng and Butler, 2013) 3-5 min (Sible and Nawarskas, 2017) 5-7 h (murine) (Zheng et al, 2016) Prodrug No Yes (CYP3A5 and CYP2C19) (Yoo et al, 2009(Yoo et al, , 2010 Yes Yes…”
Section: B Adp Receptor Inhibitorsmentioning
confidence: 99%
“…Interestingly, the utility of anfibatide has also been evaluated in preventing a fatal blood-clotting disorder, such as TTP. Intraperitoneal administration of anfibatide mitigated spontaneous thrombocytopenia and prevented a shigatoxin-induced TTP murine model (Zheng et al, 2016) (ADAMTS13-deficient mice). Although anfibatide has completed its clinical phase I for safety and efficacy in patients with non-ST elevation myocardial infarction, phase II has yet to commence.…”
Section: F Glycoprotein Ib-ix-v Inhibitorsmentioning
confidence: 99%
“…Notably, unpublished phase IIa human clinical trials have shown the promise of anfibatide as a novel antiplatelet agent without significantly affecting haemostasis in patients with non-ST segment elevation myocardial infarction (MI) 81. Additionally, anfibatide was also shown as a promising candidate to treat ischaemic stroke and spontaneous or bacterial shigatoxin-induced acquired thrombotic thrombocytopenic purpura (TTP) in experimental animal models 82 83…”
Section: Introductionmentioning
confidence: 99%
“…In a microfluidic shear model, anfibatide inhibited platelet adhesion, aggregation, and thrombosis formation under static and shear conditions and resulted in resolution of spontaneous thrombocytopenia in a Shiga toxin-induced murine TTP model. 43 However, the safety and efficacy of anfibatide for TTP treatment in human subjects requires further study in prospective clinical trials. Emerging data suggest that TTP may be associated with complement activation, perhaps through ultra-large VWFmediated effects, 44 and the successful use of the terminal complement inhibitor, eculizumab, in TTP has been reported.…”
Section: Other Novel Agentsmentioning
confidence: 99%